Naturally occurring fish poisoning illness - An evidence-based review - R. Jerlin Anusha, W. Delphin Bencer, Keerthana Chandrasekar (Journal of Applied Pharmaceutical Science, 2021)
Fish is the most common seafood in India. Many seafood poisonings are unknown due to the lack of awareness. Fish poisoning happens as a result of natural toxins which cause some serious effects on humans due to the food chain. Some toxins’ effects are useful in the medical field such as neurotoxins, which can produce paralysis effects; it is widely used as an analgesic to treat cancer pain. Under the sea, climate change and the distribution of marine toxins like dinoflagellate are the high-risk features. Diagnosis can be confirmed by testing the contaminated fish tissue or by human blood samples. Early treatment is effective in reducing mortality. Physicians play an important role in identifying fish poisoning and managing the same. This review aims to collect the pertinent information available to date on various fish poisonings and the analogues, with a special emphasis on the family, etiology, distribution, effects, diagnosis, management, and prevention.
Keywords: Fish poisoning, natural toxins, dinoflagellate, mortality, types of fishes